2012
DOI: 10.1161/strokeaha.111.621300
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya Disease in China

Abstract: Background and Purpose-Here we describe the clinical features and outcomes of patients with moyamoya disease who were surgically treated at a single institution in China. Methods-Our cohort included 802 patients with moyamoya disease. Demographic and clinical characteristics were obtained by retrospective chart review; follow-up information and outcome were obtained through clinical visits, telephone, or letter interview. We used the Kaplan-Meier methods to estimate stroke risk by treatment status. Results-The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(60 citation statements)
references
References 31 publications
3
57
0
Order By: Relevance
“…3,16 The results suggest that a sex distribution difference exists between unilateral and bilateral MMD cases, and that female preponderance may be greater in unilateral MMD than in bilateral disease. 14,18,21 One previous study, which also analyzed the sex distribution, also indicated that unilateral MMD might be influenced by acquired diseases, including autoimmune disease.…”
Section: Discussionmentioning
confidence: 86%
“…3,16 The results suggest that a sex distribution difference exists between unilateral and bilateral MMD cases, and that female preponderance may be greater in unilateral MMD than in bilateral disease. 14,18,21 One previous study, which also analyzed the sex distribution, also indicated that unilateral MMD might be influenced by acquired diseases, including autoimmune disease.…”
Section: Discussionmentioning
confidence: 86%
“…1,3) However, the differences between the clinical profiles of Korean and Japanese patients are unlikely to be explained by genetic differences. Specific factor(s) other than the genetic factor are needed to explain the variations in the clinical phenotypes and low penetrance among carriers.…”
Section: Discussionmentioning
confidence: 99%
“…7 All data were collected through March 2015. The study protocol was approved by the institutional ethics committee.…”
Section: Retrospective Chart Reviewmentioning
confidence: 99%
“…25 There is wide controversy regarding the merits and shortcomings of the 2 surgical approaches for adults with MMD. 2,5,7,23,31 Starke et al reviewed the literature concerning the surgical treatment and concluded that both direct and indirect bypass were effective. 30 Since there is a lack of randomized trials, it was noted that the selection of the surgical modalities depended on the preference and surgical technique mastered by the cerebrovascular neurosurgeon.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation